Overall avidity declines in TCR repertoires during latent CMV but not EBV infection - Couturaud, Barbara; Doix, Bastien; Carretero-Iglesia, Laura; Allard, Mathilde; Pradervand, Sylvain; Hebeisen, Michael; Rufer, Nathalie (Frontiers in Immunology, 2023)
The avidity of the T-cell receptor (TCR) for antigenic peptides presented by the MHC (pMHC) on cells is an essential parameter for efficient T cell-mediated immunity. Yet, whether the TCRligand avidity can drive the clonal evolution of virus antigen-specific CD8 T cells, and how this process is determined in latent Cytomegalovirus (CMV)-against Epstein-Barr virus (EBV)mediated infection remains largely unknown. Here, we quantified monomeric TCR-pMHC dissociation rates on CMV-and EBV-specific individual TCRab clonotypes and polyclonal CD8 T cell populations in healthy donors over a follow-up time of 15-18 years. Within CMV/pp65-specific T cell repertoires, a progressive contraction of clonotypes with high TCR-pMHC avidity and low CD8 binding dependency was observed, leading to an overall avidity decline during long-term antigen exposure. We identified a unique transcriptional signature preferentially expressed by high-avidity CMV/pp65-specific T cell clonotypes, including the inhibitory receptor LILRB1. Interestingly, T cell clonotypes of high-avidity showed higher LILRB1 expression than the low-avidity ones and LILRB1 blockade moderately increased T cell proliferation. Similar findings were made for CD8 T cell repertoires specific for the CMV/IE-1 epitope. There was a gradual in vivo loss of high-avidity T cells with time for both CMV specificities, corresponding to virus-specific CD8 T cells expressing enhanced LILRB1 levels. In sharp contrast, the EBV/BMFL1-specific T cell clonal composition and distribution, once established, displayed an exceptional stability, unrelated to TCR-pMHC binding avidity or LILRB1 expression. Together, these findings reveal an overall long-term avidity decline of CMV-but not EBV-specific T cell clonal repertoires, highlighting the differing role played by TCR-ligand avidity over the course of these two latent herpesvirus infections. Our data further suggest that the inhibitor receptor LILRB1 potentially restricts the clonal expansion of highavidity CMV-specific T cell clonotypes during latent infection. We propose that the mechanisms regulating the long-term outcome of CMV-and EBV-specific memory CD8 T cell clonotypes in humans are distinct.